Primary middle ear papilloma: A case report - Nur Izzati Ishak; Goh, Bee See; Mohammad Fariz Amri (Pakistan Medical Association, 2022)
We report a case of primary middle ear papilloma in a 66-year-old male with underlying chronic suppurative otitis media, presenting with right sided otorrhea with progressive aural mass formation. He underwent right mastoidectomy and tumour excision. Diagnosis of right middle ear papilloma with no malignant features was confirmed with histopathological examination. The patient recovered well with no recurrence up to 12 months.